Culture of teenager’s spiritual safety: definition and characterization of criteria features - Evgeny V. Krotov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper is devoted to the issues of a teenager education as a subject of spiritual culture. The purpose of this research is to study the phenomenon of the culture of teenagers spiritual safety to identify the criteria and their features. What is described in this paper is more theoretical in nature and precedes the practical part, therefore the following methods are used: analysis, comparison, contrast, study of methodological experience, generalization. To achieve this goal, we have identified the following tasks: 1) to consider the phenomenon of culture in the view of domestic pedagogy; 2) analyze the concepts related to the subject of research: spirituality, security, personal security, spiritual security; 3) on the basis of studying the characteristics of a spiritual personality, identify the criteria for the culture of teenagers spiritual security and outline the main characteristics of these criteria. Much attention is paid to traditional culture. Teenagers spiritual safety is defined as a system of conditions ensuring the preservation of important cultural parameters within the existing traditional standards. The criteria of the culture of teenagers spiritual safety have been determined. They are moral, cognitive, axiological, informational ones. Each of the criteria has indicators that reflect the formation level of teenagers certain characteristics. Socio-civic and individual-personal levels reflect the personality traits, the perfection of which we see in the culture of spiritual security. In general, mastering the culture of teenagers spiritual security is designed to contribute to the development of a creative personality. The theoretical grounds for identifying the phenomenon of the culture of teenagers spiritual safety are described in detail, the choice of criteria features is justified, and their characteristics are presented. The results contribute to theoretical pedagogy and are aimed at further development of methodological recommendations, creation of a process model and practical application.